Do Cannabis Users Reduce Their THC Dosages When Using More Potent Cannabis Products? A Review - Leung, Janni; Stjepanović, Daniel; Dawson, Danielle; Hall, Wayne D. (Frontiers in Psychiatry, 2021)
Background: Higher potency cannabis products are associated with higher risks of negative physical and psychological outcomes. The US cannabis industry has opposed any restrictions on THC levels, arguing that people titrate their THC doses when consuming higher potency products. Objective: To review research on the degree to which people who use cannabis for recreational purposes can and do titrate their THC doses. Method: A systematic search was conducted for studies published from 1973-2020. We included (1) experimental laboratory studies on dose titration of cannabis products that varied in THC content; (2) observational studies on use of more potent products; and (3) surveys on whether cannabis users titrate when using more potent products. Results: In some experiments, there were inverse associations between the THC content and the amount smoked and smoking topography, while others indicated higher doses consumed and psychological and physiological effects observed. Findings of observational studies of regular cannabis users were more equivocal. In some surveys, cannabis users reported that they use less when using more potent products, but in other surveys, persons who used more potent cannabis had more adverse effects of use. Discussion: There is some evidence from experimental studies that people who use higher potency cannabis for recreational purposes can titrate their THC doses, but less evidence that regular cannabis users do in fact do so. We a need much better experimental and epidemiological research to inform the design of regulatory policies to minimize harms from the use of high THC cannabis products.